2009
DOI: 10.1016/j.radonc.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the bifunctional suicide gene CDUPRT increases radiosensitization and bystander effect of 5-FC in prostate cancer cells

Abstract: Purpose To test a hypothesis that, with 5-fluorocytosine (5-FC) treatment, the co-expression of cytosine deaminase (CD) and uracil phosphoribosyltransferase (UPRT) can lead to greater radiosensitization and bystander effect than CD-expression alone. Methods and Materials R3327-AT cell lines stably expressing CD or CDUPRT were generated. The 5-FC and 5-FU cytotoxicity, and the radiosensitivity with/without 5-FC treatment, of these cells were evaluated under both aerobic and hypoxic conditions. The bystander e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Instead, efficacy was better with the combination, which might increase the therapeutic window of the approach because enhanced efficacy together with less virus replication might mean less replication-associated side effects. Lastly, we observed an increase in apoptosis in tumors treated with Ad5/3-Δ24FCU1 + 5-FC comparing to Ad5/3-Δ24FCU1 or 5-FC alone, confirming the mechanism of action of 5-FU and 5-FUMP (40). Because the data on apoptosis and oncolytic adenovirus replication are somewhat discordant (41)(42)(43)(44), perhaps in part due to the antiapoptotic activities of E1B and E4 (44,45), we assume that the increase in apoptosis seen here may be chiefly due to the 5-FU-mediated bystander effect.…”
Section: Discussionsupporting
confidence: 73%
“…Instead, efficacy was better with the combination, which might increase the therapeutic window of the approach because enhanced efficacy together with less virus replication might mean less replication-associated side effects. Lastly, we observed an increase in apoptosis in tumors treated with Ad5/3-Δ24FCU1 + 5-FC comparing to Ad5/3-Δ24FCU1 or 5-FC alone, confirming the mechanism of action of 5-FU and 5-FUMP (40). Because the data on apoptosis and oncolytic adenovirus replication are somewhat discordant (41)(42)(43)(44), perhaps in part due to the antiapoptotic activities of E1B and E4 (44,45), we assume that the increase in apoptosis seen here may be chiefly due to the 5-FU-mediated bystander effect.…”
Section: Discussionsupporting
confidence: 73%
“…CD and HSV1-TK, or CD and UPRT), resulting in improved tumoricidal effect for different tumors. 1215,23 Both the in vitro and in vivo data in the present study (Fig. 3–5 and supplementary Fig.…”
Section: Discussionsupporting
confidence: 66%
“…25 Previously, we have demonstrated that CDUPRT/5-FC approach has greater radiosensitization effect than the CD/5-FC system. 15 Therefore, it is not surprising that significant tumor control effects were found as triple suicide gene approach combined with radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out that combination of radiation therapy and gene therapy, called 'radio-genetic therapy' , is an attractive prospect, [11][12][13] as the combination may potentially overcome these defects of either therapy. It may use a gene whose product is capable of improving the anticancer effects of ionizing radiation, and/or controlling the expression of therapeutic genes by irradiation.…”
Section: Introductionmentioning
confidence: 99%